Physical, Chemical and Microbial Characteristic of Gouda Cheese Using Propolis (Apis milifera Liguistica) as Coating Material (Jurnal Ilmu dan Teknologi Hasil Ternak, 2011)
Gouda cheeses were coated with different coating materials consist of pliol, beeswax, and beeswax containing different concentration of propolis  by 0,2, 0,4 and 0,8%  and stored  during  ripening at 10oC period. The result showed that no different of moisture, fat and protein content, hardness, pH value of cheese products. The hydrolysis process at maturity caused decreasing of  pH value. Added propolis in the coating material could inhibited  mould and yeast growth significantly. Key words:  Gouda Cheese, propolis, edible coating